Analysis of Economic, Supply Chain Policy and Environmental Impacts on the Development of “KEK” Kelayang Cape in Belitung Island - Reniati Reniati; Endang Bidayani; Khairiyansyah Khairiyansyah (International Journal of Supply Chain Management, 2019)
The purpose of this research is to analyse the impact of the development of supply chain strategy in the tourism KEK Kelayang Cape as an alternative economy after Tin Mining. The research method is quantitative descriptive design, the number of samples used 80 SME business based on tourism. Analysis of the data using the analysis Confirmatory Factor with PLS method. Research findings indicate that the development of tourism in the Island of Belitung already provide economic impact, social and environment. The impact of the economy has 5 (five) dimensions, social impact has 5 (five) dimensions and environmental impacts have 4 (four) dimensions. The results of this analysis found that the impact of the economy is the most important dimension of measuring the impact of the development of KEK Kelayang Cape with the value of loading factor as the most high. The results of research has implications for the management practices that for economic impact absorption work force indicator is most important. Now the most important indicator of the social impact is positive changes on the values and adat isitiadat. The most important indicator of Environmental impact is the performance improvement/condition of the tourism area. Research Originality: This research conducted in the election of 1 of 10 tourism destination in Indonesia which is KEK , based on tourism in Belitung Island.